Anticorrosive waterborne paints with reduced phosphate content - Mészáros, G. (2010)
The most important challenges in the field of paint technology are concerned with the development of safer products, safer processes and reduced solvent emissions to the atmosphere with zero emissions as the goal [1]. In the case of anticorrosive paints safer products means, primarily, the complete elimination of chromates and the employment of water instead of organic solvents. In this sense, from 1970 on, two major goals were achieved in the field of paint technology: the replacement of toxic inhibitive pigments containing lead and chromate compounds by phosphates and the progressive elimination of solvents in paint formulations to fit VOC’s regulations. Three generations of phosphates were introduced in the market, being zinc phosphate the precursor [1-10]. The second generation was developed by performing suitable modifications in the zinc phosphate particle [7-14]. Finally, the third generation was designed to meet high technological applications and was obtained changing the orthophosphate anion by the tripolyphosphate one [15- 25]. Both, the second and third generation phosphate pigments are claimed to have equal or superior anticorrosive behaviour than chromates and better than zinc phosphate on its own. Other anticorrosive pigments, apart from phosphates, were found to be suitable to formulate anticorrosive paints. Among them ferrites, calcium exchanged silicas, etc [26, 27]. More recently the development of intelligent anticorrosive paints was reported [28].